La imagen devocional frente al desastre natural: una aproximación a los usos y funciones de la escultura religiosa en Cartago según fuentes históricas del siglo XVIII - Ramírez Maglione, Aniella (CIICLA, Universidad de Costa Rica, 2018)
This article exposes the interference of the landscape in the development of cultural practices during the colony, specifically analyses the implications of the material and spiritual crisis derived from the natural catastrophe, in the use and function that Inhabitants of Carthage assign to the devotional image. The comparison of primary sources of the 17th and 18th centuries allows to deduce the correspondences between religion and worldview, from which derive both forms of perception and interpretation of natural phenomena such as ritual practices that allow mitigating their effects. In this field it is intended to deepen in the cultural aspects that determine the religious images that demand greater popular fervor. In this way, the methodology implemented allows to articulate image and cult in the understanding of the colonial art.